Geo-Ethics: What to do When Approval Authority Decisions Contradict Sound Science? - Priddle, Mark (Geoscience Canada, 2017)
Three case studies in Canada are evaluated where a regulatory authority ruled that measures considered by some professionals to be without scientific basis and less protective of human health or the environment were the required courses of action. The three projects were in the field of environmental geoscience. In all three cases, the solution proposed by a Professional Geoscientist (P.Geo.) was opposed by a representative of a regulatory body that held authority for approval. The final outcomes that were approved by the Regulator were less protective of human health (increased exposure to potential contaminants) and/or the environment (more resources used, higher contaminant exposure). In two of the three cases, the solutions were also more expensive to the client and the taxpayer. This paper explores the practice of professionalism in geoscience versus regulatory authorities that hold jurisdiction over geoscience in a broad sense. In each of the three cases, the professional opinions and analysis of the P.Geo. working for a private sector client were overridden by a professional (P.Geo. or Professional Engineer) in an approval authority. These three studies highlight the ethical decisions required by professional geoscientists in the face of regulators who hold control over areas of geoscience. Although the training of professionals is similar, regulators appear to be influenced by perceived risk as opposed to actual risk based on scientific evidence. Similarly, some policies do not have a solid scientific basis. As a result, sound scientific reasoning and resulting rational decisions may be hindered in regulatory decision-making.